2015
DOI: 10.3390/molecules201219794
|View full text |Cite
|
Sign up to set email alerts
|

1-Deoxynojirimycin Alleviates Insulin Resistance via Activation of Insulin Signaling PI3K/AKT Pathway in Skeletal Muscle of db/db Mice

Abstract: 1-Deoxynojirimycin (DNJ) is widely used for the treatment of diabetes mellitus as an inhibitor of intestinal α-glucosidase. However, there are few reports about its effect on insulin sensitivity improvement. The aim of the present study was to investigate whether DNJ decreased hyperglycemia by improving insulin sensitivity. An economical method was established to prepare large amounts of DNJ. Then, db/db mice were treated with DNJ intravenously (20, 40 and 80 mg¨kg´1¨day´1) for four weeks. Blood glucose and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 56 publications
3
52
0
Order By: Relevance
“…2011 ) and elevated glucose transporter-4 (GLUT-4) translocation (Liu et al. 2015 ) in skeletal muscles and adipose tissues. These mechanisms could explain the amelioration of insulin resistance of target tissues.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…2011 ) and elevated glucose transporter-4 (GLUT-4) translocation (Liu et al. 2015 ) in skeletal muscles and adipose tissues. These mechanisms could explain the amelioration of insulin resistance of target tissues.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…1-Deoxynojirimycin (DNJ, Figure 4 ) and Kuwanon G (KWG, Figure 5 ) are the effective constituents of mulberry leaf, which belongs to the genus Morus of the Moraceae family. The chemical structure of DNJ is a glucose analogue with an NH group substituting for the oxygen atom of the pyranose ring [ 100 ]. Mulberry leaf, as a traditional Chinese medicine, has been used to treat fever and inflammation for thousands of years.…”
Section: Herbal Monomersmentioning
confidence: 99%
“…DNJ inhibits the glucose absorption through competitive inhibition of α -glucosidase [ 104 ]. In db/db mice, DNJ treatment improved insulin resistance via the activation of the insulin signaling PI3K/AKT pathway in skeletal muscle [ 100 ] and the activation of the PKB/GSK-3 β signaling pathway in the liver [ 105 ].…”
Section: Herbal Monomersmentioning
confidence: 99%
“…3B). Previous study has also demonstrated the improvement of insulin resistance improvement of insulin resistance in ob/ob mice after intravenous administration of DNJ (40). There was however, notable difference in the significance level between the fasting blood glucose level (minute 0) during the OGTT (Fig.…”
Section: Resultsmentioning
confidence: 70%